Hubungan Antara Paparan Asap Rokok dan Status Gizi (LiLA) dengan Kejadian BBLR di Puskesmas Sidotopo Kecamatan Semampir Kota Surabaya - Shela Vitara (Universitas Batanghari Jambi, 2023)
LBW (Low Birth Weight) is a health or nutritional problem that is a concern in countries with low socio- economic status, especially in developing countries like Indonesia. LBW is also one of the causes of death of a baby in the first month of birth. In general, the incidence of LBW is caused by maternal factors (nutrition status MUAC (upper arm circumference), fetal factors and placental factors. In addition, there are environmental factors that can cause LBW, namely exposure to cigarette smoke. The purpose of this study was to analyze the relationship between exposure to cigarette smoke and nutritional status (MUAC) with the incidence of low birth weight in the Sidotopo Health Center area, Semampir District, Surabaya City. This research is an analytic observational type research where the researcher does not provide treatment to the intended subject. In addition, the research design used is case control. The study sample is 38 people were taken randomly using simple random sampling. Primary data collection included filling out a cigarette smoke exposure questionnaire.Meanwhile, secondary data collection included nutritional status data (MUAC) contained in the mother's KIA book. Data analysis used in this study was chi-square The results showed that there was a relationship between the nutritional status (MUAC) of mothers (p=0.004) in the case and control groups and the incidence of LBW in the Sidotopo Community Health Center, while exposure to cigarette smoke (p=0.693) in the case and control groups had no relationship with the incidence of LBW. in the Sidotopo Community Health Center. The conclusion from this study is that there is still a lack of MUAC nutritional status measures (<23.5 cm) in pregnant women which can be a risk cause or support for LBW events in infants. It is better to do socialization about LBW and programs for pregnant women and WUS (women of childbearing age). The programs that can be carried out are socialization about the dangers of cigarette smoke to prospective mothers and husbands and improving nutritional status (MUAC) for prospective pregnant women.